Psoriatic Dermal-derived Mesenchymal Stem Cells Reduce Keratinocyte Junctions, and Increase Glycolysis - Junqin Li; Jianxiao Xing; Funa Lu; Wenjuan Chang; Nannan Liang; Juan Li; Ying Wang; Xiaofang Li; Xincheng Zhao; Ruixia Hou; Maoqiang Man; Guohua Yin; et al. (Medical Journals Sweden, 2020)
Although it is known that psoriatic dermal-derived mesenchymal stem cells (DMSCs) dysregulate keratinocyte proliferation, the biological activity profile of keratinocytes influenced by psoriatic DMSCs remain unknown. In the present study, we assessed the impact of psoriatic DMSCs on keratinocyte proliferation, differentiation, and glucose metabolism in normal human epidermal keratinocytes co-cultured with or without psoriatic DMSCs. Co-culture of normal human epidermal keratinocytes with psoriatic DMSCs downregulated expression levels of proteins associated with cell junction assembly (alpha-actinin-1, catenin beta-1, poliovirus receptor-related protein 4 and procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2), while upregulating proteins associated with keratinocyte proliferation and differentiation (involucrin, isoform 2 of Histone-binding protein, isoform 3 of Telomeric repeat-binding factor 2 and keratin 13). Moreover, co-culture of normal human epidermal keratinocytes with psoriatic DMSCs stimulated keratinocyte proliferation and glycolysis, but reduced keratinocyte junctions. Taken together, these results demonstrate that psoriatic DMSCs increase keratinocyte proliferation and glycolysis, and reduce cell junctions, suggesting a pathogenic role of psoriatic DMSCs in epidermal hyperplasia, aberrant differentiation, and reduction in turnover time of keratinocytes in psoriasis.